Racism in Othello - mutlu, kader (Journal of History Culture and Art Research, 2013)
Racism has been one of the most devastating matters of the human being from the very beginning of the history, and it has been a topic of great debate and discussion since then. This severe fact does not have a special time and place. Actually, every society that has inhabited the earth has been virtually affected by this dispensable problem, racism. As all the important affairs of human being, the issue of the race is also one of the most significant themes that have a huge place in world- wide literature. Generally, most of the eras in the literature world have got their share of pleasure from this subject but Elizabethan Era was one of the most obvious times and Elizabethan Society was one of the most obvious places that discrimination of race was felt. The fascinating play of Shakespeare, Othello, is one of the plays that are shaped by the flaming effects of Racism. The unavoidable and destructive effects of racism on people’s lives and how a society that has the prejudice of racism can restrain love and what can be the limitation of the racist people at destroying the people’s happiness are constructing the main purpose and progress of this research. It is to touch on the bad development of a character that has the bad feeling of racism and shaping his life according to it even dedicating himself to working under the devastating power of the racism.